Optimizing Straw Mushroom Production through Risk-Based Decision-Making: Insights from the House of Risk Approach - Wulandari, Novi Diah; Fadli, Muhamad Dziaul; Pratiwi, Nurna (Economics, Business, Accounting & Society Review, 2025)
Risk of production in straw mushroom cultivation has become a critical concern due to its vulnerability to environmental fluctuations, pathogen contamination, and unstable market conditions. These risks have led to declining yields and quality, particularly for smallholder enterprises in Indonesia. This study aims to analyze the risks in straw mushroom production at Oemah Jamur using the House of Risk (HOR) model while also examining the role of digital tools in mitigating priority risks. The research employed a mixed-methods approach by integrating interviews, field observations, and secondary data to identify potential risk events. The HOR model was applied in two stages: first, to map and quantify risk agents using Aggregate Risk Potential (ARP), and second, to prioritize mitigation actions based on their effectiveness-to-difficulty ratio. Data triangulation was used to strengthen the validity of findings, and Pareto analysis was employed to highlight the most influential risks. The process enabled systematic identification of 13 risk events and 16 risk agents, leading to the determination of 10 priority risks. The main results show that fluctuations in temperature, humidity, and lighting were the most critical risks, and the adoption of an automatic climate control system offered the most effective mitigation. Additionally, IoT-based monitoring, standardization of pasteurization, and improved ventilation significantly enhanced environmental stability. These findings imply that combining structured risk analysis with digital solutions can improve the efficiency, sustainability, and competitiveness of straw mushroom production.